First ecological data of flying foxes of the genus Pteropus (Chiroptera: Pteropodidae) in Vietnam - Thong, Vu Dinh; Tung, Nguyen Thanh; Thanh Tinh, Nguyen Tran (Academia Journal of Biology, 2015)
Flying fox is the common name of all fruit bat species of the genus Pteropus. Prior to this study, Vietnamese flying foxes were poorly studied and their ecology was almost unknown. To fill this gap, we conducted monthly surveys between January and September 2014 in Soc Trang province with emphasis on variations of colony size, diet and roosting behavior of flying foxes. The surveys included observational counting, field identification of flying foxes and identification of food samples and their roosting trees. Results from the surveys indicated that the colony comprises two species, the larger of which is Pteropus lylei and the smaller one is provisionally identified as Pteropus cf. hypomelanus. Although there are nearly one thousand trees in the study site, flying foxes roost under the canopies of very few. The colony size varies weekly, monthly and seasonally with a total number of individuals ranging between 453 in April and 1,753 in February. This paper also provides a risk assessment and recommendations for urgent conservation of these threatened mammals.